Enhanced focal-resolution of dipole sources using aeroacoustic time-reversal in a wind tunnel. (May 2016) - Mimani, A.; Moreau, D.J.; Prime, Z.; Doolan, C.J.
Abstract: This paper presents the first application of the Point-Time-Reversal-Sponge-Layer (PTRSL) damping technique to enhance the focal-resolution of experimental flow-induced dipole sources obtained using the Time-Reversal (TR) source localization method. Experiments were conducted in an Anechoic Wind Tunnel for the case of a full-span cylinder located in a low Mach number cross-flow. The far-field acoustic pressure sampled using two line arrays of microphones located above and below the cylinder exhibited a dominant Aeolian tone. The aeroacoustic TR simulations were implemented using the time-reversed signals whereby the source map revealed the lift-dipole nature at the Aeolian tone frequency. A PTRSL (centred at the predicted dipole location) was shown to reduce the size of dipole focal spots to 7/20th of a wavelength as compared to one wavelength without its use, thereby dramatically enhancing the focal-resolution of the TR technique.